Sustainable Urban Housing in China Principles and Case Studies for Low-Energy Design - Glicksman, Leon.; Lin, Juintow; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2006)
ENCOUNTERING SUSTAINABILITY IN CHINA Yung-Ho Chang What I am writing is by no means a typical foreword. Instead of introducing the work outside of Beijing, we enclosed a courtyard with buildings and hillside to create a of my colleagues in the Department of Architecture at Massachusetts Institute of milder microclimate. We also employed two traditional materials, earth and wood, Technology (MIT), I will use this opportunity to share my own limited but critical specifically rammed-earth walls and laminated wood frames, to build a structure that experience with the development of sustainability in China. However, I would like to is capable of disintegration and would produce less waste once the house is no longer point out that the authors of this book are among the pioneers for sustainability needed. Although ancient wisdom, rather than advanced technology, was engaged, research and design in China, and they have helped to build the foundation of an we were able to address the issue of sustainability for the first time. After all, ecologically sensitive architecture in China. sustainability is about a way of thinking. Step II. UFIDA R&D Center, Beijing: For this project for a software company, the A CHANGING PRACTICE sustainable design focused on the reorganization of workspaces. The circulation system was transformed into public areas where communication and socialization is As an architect in China, I have been confronted by the issue of sustainability and encouraged and located in zones that receive more daylight and better views.
Background -- Sustainability and the Building Sector -- China — Environment and Culture -- Design Principles -- Design Principles for Sustainable Urban Housing in China -- Materials and Construction for Low-Energy Buildings in China -- Technical Findings -- Low-Energy Building Design -- Wind in Building Environment Design -- Design of Natural Ventilation with CFD -- Light and Shading -- Case Studies -- Case Studies -- Case Study One — Beijing Prototype Housing -- Case Study Two — Beijing Star Garden -- Case Study Three - Shanghai Taidong Residential Quarter -- Case Study Four - Shenzhen Wonderland Phase IV -- Case Study Five — Beijing Hui Long Guan -- Future Steps -- Future Steps.
Keywords: Mechanical engineering; Geography; Architecture; Environment; Mechanical Engineering; Geography, general; Architecture, general; Cities, Countries, Regions; Environment, general